The Effect of Learning Principles on the Quality of Early Children's Learning in Pendopo District, Empat Lawang Regency - Almarizka, Jihan Ayu; Darsinah, Darsinah (Early Childhood Research Journal (ECRJ), 2022)
The purpose of this study was to determine 1) the effect of learning principles on the quality of learning. 2) effective contribution of learning principles to the quality of learning. This research is a quantitative descriptive research. The population is 72 teachers from 13 kindergartens in Pendopo District. A sample of 61 teachers was taken using the Slovin formula, the sampling technique used was proportional random sampling. Collecting data from the principles of learning and the quality of learning using a questionnaire. Data were analyzed using simple linear regression. The results of the study show that: 1) there is a positive influence between the application of learning principles on the quality of learning. 2) the effective contribution of the application of learning principles to the quality of learning is 65.1%, while the remaining 34.9% is from variables not examined.